Comparative Study of Three Different Adsorbent-Adsorbate Working Pairs for a Waste Heat Driven Adsorption Air Conditioning System Based On Simulation - H. R., Ramji; S. L., Leo; I. A. W., Tan; M. O., Abdullah (International journal of recent research and applied studies, 2014)
In a previous study, a laboratory prototype of a thermal-driven adsorption air conditioning system employing activated carbon as adsorbent and methanol as the refrigerant was successfully developed. The experimental results employing the prototype obtained a COP of 0.19 and cooling capacity Q of around 320 kJ. The cooling power P yielded ~ 0.64 kW and it was able to produce chilled air temperature Tchill,out of around 22 °C. In the present study, further works are conducted via simulation to carry out “what-if” analysis viz. to determine the optimal adsorbentadsorbate working pair based on the prototype. Three types of refrigerants, coupled with activated carbon, were considered in this study, namely (1) methanol (similar to the experimental works); (2) ammonia; and (3) water. The simulation results obtained showed that activated carbon-water pair produced the best cooling compared to activated carbon-methanol and activated carbon-ammonia working pairs, as far as present study is concerned. The methanol and ammonia showed a COP of 0.37 and 0.4, respectively. The average Tchill,out produced by methanol was around 15 °C while the temperature produced by ammonia was slightly higher around 19 °C. The cooling capacity P for methanol and ammonia showed a value of 0.65 kW and 0.50 kW, respectively. Activated carbon-water pair simulated to yield a higher COP of 0.58 with Q at 480 kJ mainly due to high heat of evaporation, which was able to produce average Tchill,out of 12 °C with cooling power of approximately 1 kW.